Application of response spectrum technique to arch dams : evaluation of superposition methods - Ho, Iuan-ming; Wireland, Martin; Loo, Yew-Chaye; Usami, Tsutomu; Chines Petroleum Corporation, R.O.C. (Bangkok : Asian Institute of Technology, 1983)
Nowadays, the response spectrum technique is widely used in practice for the earthquake analysis of buildings adopting the square root sum of squares superposition of modal response parameters. However, it is not admissible to apply the same method in its original form to other types of structures, such as arch dams which have different response characteristics. Different superposition techniques are compared for the earthquake analysis of arch dams for empty reservoir condition. Dam-foundation interaction effects are disregarded. In the first step, time-history analyses of two existing arch dams in Thailand (Bhumiphol Dam) and Taiwan (Feitsuiku Dam) are carried out, in order to evaluate the response which is used as basis of comparison for the response spectrum technique. In the second step, the following superposition methods are tested: absolute sum rule; square root sum of squares rule; p-norm rule (p=1.8, 1.9, 2.1, 2.2) : and the complete square root sum of squares seems to be the best for evaluating the stress and displacement response of arch dams. After identifying the best superposition technique it becomes possible to apply the response spectrum technique with confidence to arch dam. Relatively inexpensive methods of dynamic analyses become more important as hydro-electric schemes are being planned in may regions with high seismic activity, most of them in developing countries.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Structural dynamics; Dams -- Earthquake effects